1995
DOI: 10.1111/1523-1747.ep12605898
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Homozygous One-Basepair Deletion in Exon 14 of the LAMB3 in a Patient with Herlitz Junctional Epidermolysis Bullosa and Prenatal Diagnosis in a Family at Risk for Recurrence

Abstract: Herlitz junctional epidermolysis bullosa, a severe epidermal blistering disorder, is inherited in an autosomal recessive manner. It has recently been shown that, in kindreds with junctional epidermolysis bullosa, the disorder results from mutations in the gamma 2 chain of laminin-5, a basement membrane protein synthesized by the basal cells of stratifying squamous epithelia. In this report we describe a mutation identified in the beta 3 chain gene of laminin-5 in a family with Herlitz junctional epidermolysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
3

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 23 publications
1
36
0
3
Order By: Relevance
“…We have similarly shown that the presence of Type IV Collagen can support the early stage of BM maturation and lead to normalization of tissue organization and optimization of cell growth and survival. Thus, it appears that the balance between degradation and stabilization of newly synthesized BM components is essential for BM assembly and maturation (Amano et al 2001) It has been shown that pre-existing BM proteins serve as a template for the deposition and integration of newly synthesized proteins at the dermal-epidermal junction (Vailly et al, 1995). HSEs constructed by seeding keratinocytes on an interface containing pre-existing BM components, such as de-epithelialized skin (Andriani et al 2003) or amniotic membrane (Yang et al 2006) promote rapid assembly of well-structured BM.…”
Section: Discussionmentioning
confidence: 99%
“…We have similarly shown that the presence of Type IV Collagen can support the early stage of BM maturation and lead to normalization of tissue organization and optimization of cell growth and survival. Thus, it appears that the balance between degradation and stabilization of newly synthesized BM components is essential for BM assembly and maturation (Amano et al 2001) It has been shown that pre-existing BM proteins serve as a template for the deposition and integration of newly synthesized proteins at the dermal-epidermal junction (Vailly et al, 1995). HSEs constructed by seeding keratinocytes on an interface containing pre-existing BM components, such as de-epithelialized skin (Andriani et al 2003) or amniotic membrane (Yang et al 2006) promote rapid assembly of well-structured BM.…”
Section: Discussionmentioning
confidence: 99%
“…N-terminal amino acid sequence determinations were performed upon proteins transferred to polyvinylidene difluoride as previously reported (29,32). Fetal calf stomach skin was taken from a fetus determined by crown-rump measurements to be equivalent to the first to second trimester transition.…”
Section: Other Methodsmentioning
confidence: 99%
“…Além disso as complicações da fetoscopia com biópsia ocorrem entre quatro e 7% dos casos, e na biópsia coriôni-ca em 1%. 43 O seqüenciamento genético já foi utilizado no DPN de todas as formas de EB, 23,24,43,[49][50][51] já tendo sido também realizado antes da implantação, a partir de célula obtida de embrião com número de células variável de cinco a oito. 52 Aconselhamento genético é outra aplicação importante dessas novas informações, pois ajuda a esclarecer o padrão de herança, principalmente tratando-se de mutações freqüentes e bem conhecidas.…”
Section: Discussionunclassified
“…21,22 Semelhante às mutações dos componentes do hemidesmossoma descritas acima, as mutações da laminina também provocam o descolamento da epiderme. A maior parte das mutações dos gens da laminina 5 leva à PTC, provocando ausência da proteína e quadro clínico intenso, 23,24 caracterizado por lesões disseminadas afetando também as mucosas, 23 com sobrevida curta em função das complicações bacterianas, denominadas EBJ tipo Herlitz ou EBJ letal.…”
Section: Epidermólise Bolhosa Juncionalunclassified